Análisis antropológico visual de la cultura de la parroquia Quisapincha de la provincia Tungurahua para su aplicación en un documental turístico - Chuquiana Toroshina, José Luis (2024)
The purpose of this research is to analyze the visual anthropology of the Quisapincha parish of the Tungurahua province as a substantial descriptive element for the proposed tourist video documentary. Showing their experiences, customs and traditions throughout the year, we find festivities such as Inti Raymi, San Antonio de Padua, Festival in honor of the Virgin of Quinche, Caporales or festival of the Three Wise Men, celebrations where the Yumbos participate, Wayanas, Kurikingues, Danzantes, characters typical of the location. To collect information, interviews and observation sheets were used which allowed us to learn about elements of the culture and tradition of the Quisapincha parish. Thanks to the collaboration of the people who actively participated in the data collection process, it was possible to have a final product that will allow a better approach to the community with its roots, at the same time as it constitutes a tool to improve the tourist quality of the parish, especially in times where a better economic income is necessary for its inhabitants.